2015
DOI: 10.1007/s11255-015-1127-5
|View full text |Cite
|
Sign up to set email alerts
|

Excellent graft and patient survival after renal transplantation from donors after brain death with acute kidney injury: a case–control study

Abstract: Kidneys from AKI donors can be transplanted with excellent intermediate prognosis and should not be discarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…In light of the overall evidence supporting the use of AKI kidneys across studies, [17][18][19][20][21][22][23][24][25][26] the concerns raised by the registry study 48…”
Section: Discussionmentioning
confidence: 99%
“…In light of the overall evidence supporting the use of AKI kidneys across studies, [17][18][19][20][21][22][23][24][25][26] the concerns raised by the registry study 48…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited retrospective data on the outcome of kidneys with donor AKI in Germany [1214]. All studies are small and have several limitations i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although donation after circulatory death (DCD) is associated with significantly higher incidences of DGF, midterm survival of DCD kidneys is comparable to those from DBD . There is accumulating evidence that AKI occurring under warm circulatory conditions in the DBD, and progressing to DGF after transplantation hardly worsens midterm graft outcomes . A large register‐based study from the United Kingdom reported a 2% reduction only in 1‐year kidney graft survival from donors with AKI .…”
Section: Discussionmentioning
confidence: 99%